Employing Design and Development Research (DDR) Approches in Traceability Model For Test Effort Estimation To Support Software Change Management - Rejab, Mazidah Mat; Jamil, Mohd Ridhuan Mohd (International Journal of Computer Sciences and Engineering, 2022)
In the last decade, the management of software projects has become a challenging task. The latest published figures on the status of software projects indicate a large failure rate, which has created a crucial challenge for project managers. In software maintenance, the impact of software changes is an important aspect due to the evolving environment of the software development life cycle. Many of the current traceability approaches and tools are devoted to and restricted to high-level objects such as specifications but fewer capabilities are made available to handle lower-level artefacts such as classes and codes. While test effort estimation has been in place for decades, it remains a major challenge for software project management to make accurate estimates and, ultimately, to successfully complete the software project. This article proposed a novel traceability model for test effort estimation to support software change management employing Design and Development Research (DDR), which may assist software project managers in making more informed decisions on software change management. In this paper will show two phase Fuzzy Delphi Method (FDM) and Nominal Group Technique (NGT) result. The both results in FDM and NGT showed that the key components and elements are located at acceptable level and can be applied whilst the score of more than 70% is achieved. Hence, the evaluation results proved that the proposed model and its prototype are acceptable and significant to support software change management.